2009
DOI: 10.1007/s11199-009-9643-3
|View full text |Cite
|
Sign up to set email alerts
|

College Students’ Descriptions of Everyday Gender Prejudice

Abstract: This study examined 104 undergraduate college students (mean age = 19) from the Western United States regarding gender differences in their experiences of gender prejudice. Women (N=81) and men (N=22) responded to an online diary for 14 days, resulting in 1008 descriptions of events. Women reported significantly higher levels of negative affect than men during the experiences. Qualitative content analysis was used to analyze event descriptions and three main themes emerged including target of the event, perpet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 64 publications
(68 reference statements)
0
42
0
Order By: Relevance
“…Participants Data for the present study were derived from a larger study in which college students responded to an online diary for 14 days regarding their experiences of gender prejudice (See also Brinkman and Rickard 2009). Eighty-one women from a large western university attended the primary research session where they completed the demographic questionnaire and were given instructions about using the online diary.…”
Section: Methodsmentioning
confidence: 99%
“…Participants Data for the present study were derived from a larger study in which college students responded to an online diary for 14 days regarding their experiences of gender prejudice (See also Brinkman and Rickard 2009). Eighty-one women from a large western university attended the primary research session where they completed the demographic questionnaire and were given instructions about using the online diary.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in the United States, 2008 presidential campaign in the United States had the potential to have two unknown possibilities: a White female or a Black male for the presidential nomination. Apparently, the less risky unknown was to nominate a Black male as opposed to a White female (Brinkman & Rickard, 2009;Brinkman, Garcia, & Rickard, 2011;Garcia-Retamero & Lόpez-Zafra, 2006;Lehman, 2012;Leppel, 2001;Nadal, Davidoff, Davis, Wong, Marshall, & McKenzie, 2015;Stefurak, Taylor, & Mehta, 2010). ISSN 2329-9150 2016 …”
Section: Gendermentioning
confidence: 99%
“…Recent research has established that STEM academic programs have traditionally shown discrimination and prejudice toward female students (Berryman-Fink, 2006;Brinkman & Rickard, 2009;Brinkman, Garcia, & Rickard, 2011;Deemer, Smith, Carroll, & Carpenter, 2014;Garcia-Retamero & Lόpez-Zafra, 2006;Lehman, 2012;Leppel, 2001;Levin, Van Laar, & Sidnaius, 2003;Nadal, Davidoff, Davis, Wong, Marshall, & McKenzie, 2015;Rice, Lopez, Richardson, & Stinson, 2013). One such academic discipline, business, traditionally over-represents White males.…”
Section: College Majormentioning
confidence: 99%
“…However, many of the potentially sexist interpersonal behaviors that women encounter in their daily lives such as cat-calls (Chaudoir & Quinn, 2010), lewd remarks, and objectifying gazes (Gervais, Vescio, & Allen, 2011;Saguy, Quinn, Dovidio, & Pratto, 2010;Swim et al, 2001;Brinkman & Rickard, 2009) do not fall squarely within standard conceptualizations of hostile or benevolent sexism. Whereas hostile and benevolent sexism relies on stereotypes and prescribed social roles based on gender group membership to subordinate women (Glick & Fiske, 1996), sexual objectification-behaviors that reduce women to mere body parts designed for the consumption of others (Fredrickson & Roberts, 1997)-relies upon changes in perceptual processes.…”
Section: Type Of Commentmentioning
confidence: 99%